The Role of Organizational Justice on Perceived Organizational Support At Indonesian Ports - Jimmy Nikijuluw; Syarifudin Tippe; Mahmuddin Yasin (Journal of International Conference Proceedings (JICP), 2019)
Employees at Indonesian ports need support from the organization to be able to make quick and right decisions. Organizational justice in this study in terms of distributive justice and procedural justice. The purpose of this study was to determine the influence of distributive justice and procedural justice on perceived organizational support. This study used 214 employees at Indonesian Ports. The results show that distributive justice has a significant and positive impact on perceived organizational support. Procedural justice also has a significant and positive effect on perceived organizational support. The implication of this research is for the port industry to continue to pay attention for perceived organizational support by considering distributive justice because it has the most influence.